2019
DOI: 10.1080/24748706.2019.1639234
|View full text |Cite|
|
Sign up to set email alerts
|

Myocardial Injury Post Transcatheter Aortic Valve Implantation Comparing Mechanically Expanded Versus Self-Expandable Versus Balloon-Expandable Valves

Abstract: Background: Myocardial injury (MI) is common with transcatheter aortic valve implantation (TAVI) and may predict poor outcome. We aim: 1) to evaluate the difference in change of high-sensitivity-Troponin-T (hsTnT) within 24h after transfemoral-TAVI between mechanically-expanded (MEV), self-expanding (SEV) and balloon-expandable-valves (BEV); 2) to determine predictors for MI post-TAVI; and 3) to assess whether MI is associated with 30-day mortality.Methods: This multicenter retrospective observational study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…In agreement with previous data, we demonstrate an association between PPMI and higher LVEF, probably because viable myocardial tissue results in higher enzymes release, and also with worse baseline kidney function [8,[22][23][24], whereas we could not observe an independent association between PPMI and pre-TAVR valvuloplasty, mean procedural duration, and previous MI or CAD as reported in other cohorts [8,9,17,[22][23][24], probably due to heterogenous sampling and selection biases. PPMI has a mainly procedural origin, related to mechanical trauma to the myocardium due to contact with valve struts, potential multiple episodes of hypotension during valve release, and myocardial ischemia due to balloon valvuloplasty and/or valve implantation itself [15,17].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In agreement with previous data, we demonstrate an association between PPMI and higher LVEF, probably because viable myocardial tissue results in higher enzymes release, and also with worse baseline kidney function [8,[22][23][24], whereas we could not observe an independent association between PPMI and pre-TAVR valvuloplasty, mean procedural duration, and previous MI or CAD as reported in other cohorts [8,9,17,[22][23][24], probably due to heterogenous sampling and selection biases. PPMI has a mainly procedural origin, related to mechanical trauma to the myocardium due to contact with valve struts, potential multiple episodes of hypotension during valve release, and myocardial ischemia due to balloon valvuloplasty and/or valve implantation itself [15,17].…”
Section: Discussionsupporting
confidence: 90%
“…PPMI has a mainly procedural origin, related to mechanical trauma to the myocardium due to contact with valve struts, potential multiple episodes of hypotension during valve release, and myocardial ischemia due to balloon valvuloplasty and/or valve implantation itself [15,17]. Of note, we found that SEV implantation might be associated to a higher risk of PPMI has already been reported, but mainly as a collateral result, and without adjustment for other procedural and clinical variables [8,17,[22][23][24]. We employed a rigorous analytic approach that included multivariable and non-parsimonious propensity-weighted analysis: the important implication of our study, thus, is that, when the choice of implanting a SEV is made, a two-to threefold higher risk of PPMI should be accounted.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations